Boron-doped Ni/SBA-15 catalysts with enhanced coke resistance and catalytic performance for dry reforming of methane - Singh, Sharanjit; Nguyen, Trinh Duy; Tan, Ji Siang; Phuong, Pham T. T.; Nguyen, Huu Huy Phuc; Truong, Quang Duc; Lam, Su Shiung; Vo, Dai-Viet N. (Elsevier Ltd., 2020)
Nickel-based heterogeneous catalysts have shown promising results in many industrial-scale catalytic reforming processes and hydrocarbon reforming reactions such as dry reforming of methane (DRM). However, it is also reported that Ni-based catalysts generally show less resistance to the carbonaceous deposition, which ultimately causes their rapid deactivation during the reaction. One possible solution to improve the coke resistance is the addition of a promoter to the catalyst, which has shown successful results to reduce the coke formation. Therefore, this study also aimed to prepare boron-promoted Ni-based catalysts and investigate their efficiency for DRM reactions. A series of different catalysts with 10% nickel and x% boron (x: 1%, 2%, 3%, and 5%) were prepared by using an ordered mesoporous silica as a support and tested in DRM. The results demonstrated that boron-promoted Ni/SBA-15 catalysts obtained significant catalytic activity for CH4 and CO2 conversions. Meanwhile, it was noticed that a lower concentration of boron (1 and 2%) was more favourable to achieve higher catalytic activity, whereas the higher concentration (3% and 5%) resulted in a comparatively lower conversion for CH4 and CO2. Evidently, the higher activity of 2% B-promoted catalyst was ascribed to the synergistic effect of high surface area and lower crystallite size that greatly improved the active sites accessibility. Moreover, the results confirmed 14% carbon deposition on unpromoted (NS) catalyst and it was reduced to 1.3% for 2% boron-promoted catalyst owing to the presence of B-OH species on catalyst surface.